The world - change revolutions (2005)
The article presents some lines about the great social drifts that are changing the world and results into the idea of a international and unified development. In the 80´s we can see 5 great drifts that are revolutionizing the world: the first one is the economic and financial revolution, characteristic by the market´s globalization, like a new way of accumulation; the second one is the informatics revolution supported by the changes in science and technologies, basically in telecommunications. The third one is more related to the politics revolution, the disappearing of the bipolar world and the United States´s hegemony. The fourth one is the revolution of social participation and the fifth one is the revolution of urbanization.